Research Overview of German Speaking Countries - Monika Nöcker-Ribaupierre (Voices, 2013)
Abstract: This paper provides a first overview on music therapy research in Austria, Germany and Switzerland as given by the heads of the different universities in December 2012. For material collection three questions were sent to all university training course leaders. They were asked about a list of all research projects in the resp. university including MA and PhD thesis – to summarize past and ongoing research projects – to name ongoing and future research projects in cooperation with other institutions, universities or clinics.